The acceleration of DaD in pandemic times - Di Giorgi, Cristiana (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The dissemination of Covid-19 has put the education system to the test, offering the opportunity for a sudden experiment in distance learning. The survey carried out by the DITES Research Centre, of the Link Campus University, in collaboration with the Roma Tre University, ANP, FAF and AIDR provides food for thought on an irreversible didactic innovation process (Capogna et. al., 2021). Distance learning at the time of Covid-19: the point of view of university teachers and students by Maria Francesca Renzi, Roberta Guglielmetti Mugion, Laura Di Pietro, Veronica Ungaro, Maria Giovina Pasca describes the results of the research conducted on students and university teachers. The study, an excerpt of which is given here, is part of a larger project developed with the aim of investigating the education system and changes in progress.